Using electrocardiogram electrodes to monitor skin impedance spectroscopic response when skin is subjected to sustained static pressure - Emily J. Owen; Hollie Hathaway; Bronwen Lafferty; A. Toby A. Jenkins (Wiley, 2023)
Abstract Background Impedance spectroscopy is a non‐invasive technique which can be used to monitor skin barrier function, with potential applications in early‐stage pressure ulcer detection. This paper describes how changes in skin impedance, due to mechanical damage of the stratum corneum by tape stripping or applied pressure, can be straightforwardly measured using commercial electrocardiogram electrodes and a relatively low‐cost impedance analyser. Two models of pressure injury were studied, an ex vivo porcine and in vivo human skin model. Objectives Determine whether impedance spectroscopy may have potential utility in measuring the effect on skin of applied pressure on early‐stage pressure injury. Methods Two models were utilized to measure the effect of pressure. Porcine model: 0, 7.5, 15 or 22.5 mmHg of pressure was applied for up to 24 h (N = 4) and monitored at various time intervals. Human Model: 88 mmHg of pressure was applied for four sets of three‐minute intervals (N = 13) and post‐pressure recovery was monitored for 4 h. For each model, skin impedance was monitored at 0.1 Hz-50 kHz using disposable Ag/AgCl electrodes. The data was analysed using Ordinary One‐Way Analysis of Variance. Results Porcine model: after 24 h, the impedance of pressure‐loaded skin was significantly reduced compared to the non‐loaded control group (p ≤ 0.0001); this reduction in impedance was proportional to the degree of mechanical loading. Histology images of skin cross‐sections provided qualitative evidence that the epidermis was structurally compromised by pressure. Human Model: the response of healthy skin to applied pressure displayed inter‐variation. Participants with a significant change in skin impedance (p ≤ 0.01) also demonstrated signs of erythema. Conclusions This study suggests that using impedance spectroscopy to measure skin (stratum corneum) resistance may have utility in giving early warning of skin pressure injury prior to clinical symptoms, with a good correlation between observed erythema and reduction in skin resistance. Further work should be initiated on patients at risk of pressure injury to improve intervention strategies, including in darker skin tones where early‐stage pressure injuries may not be visually distinct.